Tailoring cells for clinical needs: Meeting report from the Advanced Therapy in Healthcare symposium (October 28–29 2017, Doha, Qatar) - Sara Deola (58113) (2018)
New technologies and therapies designed to facilitate development of personalized treatments are rapidly emerging in the field of biomedicine. Strikingly, the goal of personalized medicine refined the concept of therapy by developing cell-based therapies, the so-called “living drugs”. Breakthrough advancements were achieved in this regard in the fields of gene therapy, cell therapy, tissue-engineered products and advanced therapeutic techniques. The Advanced Therapies in Healthcare symposium, organized by the Clinical Research Center Department of Sidra Medicine, in Doha, Qatar (October 2017), brought together world-renowned experts from the fields of oncology, hematology, immunology, inflammation, autoimmune disorders, and stem cells to offer a comprehensive picture of the status of worldwide advanced therapies in both pre-clinical and clinical development, providing insights to the research phase, clinical data and regulatory aspects of these therapies. Highlights of the meeting are provided in this meeting report. Other Information Published in: Journal of Translational Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s12967-018-1652-y